Kreativitas dalam Tata Ruang: Membangun Perpustakaan Sekolah yang Berbasis Rekreasi di Perpustakaan Lontara Rumbia SMK Negeri 2 Jeneponto - Salmia; Tangngareng , Tasmin; Mathar, M. Quraisy (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to explore the creativity in spatial design as an effort by librarians to create a recreation-based library space at the Lontara Rumbia Library, UPT SMKN 2 Jeneponto. The research utilizes a qualitative descriptive method, with data collected through direct observations and in-depth interviews with librarians, vice-principals, and the school principal. Data analysis involves the collection, reduction, evaluation, and critical interpretation of data to reach conclusions. The results show that the recreation-based spatial arrangement at the Lontara Rumbia Library, UPT SMKN 2 Jeneponto, has developed through the initiative and support from various stakeholders. Strong support from the school, including the principal and vice-principal, has enabled the realization of a comfortable and enjoyable room design. The layout and interior of the room emphasize both physical and psychological aspects. The space is designed to meet needs such as lighting, temperature, and pleasing decoration. Complete recreational facilities, such as a reference reading room, multimedia room, and photo studio, enhance the library's appeal. Librarian innovations, such as 3D wall paintings, have transformed the perception of the library from a boring place to an attractive recreational facility.